Manusia dalam Perspsektif Agama Islam - sada, Heru Juabdin (Universitas Islam Negeri Raden Intan Lampung, 2016)
Humans are creatures of Allah the Almighty, created in a perfect state bentuk yang. Humans are spiritual beings who would have undergone various phases of events in his life before birth, present, or after death. This sentence may seem too philosophical, but actually is a term that is simple to understand. Spiritual is a psychological aspect which was then able to give strength to the people to be better able to understand life. Interest Man was created to implement the values of the divine that contain lots of serious benefits in life. Humans carry the mission mandate from Allah SWT. that must be implemented in real life activities.While the close relationship of man with Islam the man has the main task of which is to worship only God. All forms of worship that do man in various ways, all of it would go back just to us. Submissive and obedient to Allah, by becoming Caliph practice their religion, and a few other things ranging from the largest to the smallest thing that included worship is not something that is lightweight, can be done by playing let alone to deny it. Need extra effort, and spirit strong when faith is weakening, and the enormous responsibility later in the day of Judgement on what we have done in the world.